Desenvolvimento e caracterização de nanopartículas híbridas de lecitina/quitosana para liberação modificada da progesterona - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
Progesterone (PG) is a steroid hormone that plays a crucial role in the female reproductive system. Although vaginal administration represents the most effective route, its therapeutic efficacy is limited by its instability in acidic pH, low aqueous solubility, and the self-cleaning mechanisms of the vaginal mucosa. To address these challenges, self-assembling nanoparticles based on lecithin (LC) and chitosan (CS) were developed as promising carriers for PG encapsulation, aiming at vaginal delivery.The nanoparticles were synthesized using the ethanol injection technique and optimized through a 3² factorial design to assess the influence of chitosan (factor A) and PG (factor B) concentrations on the physicochemical properties of the nanoparticles. The formulations were characterized by dynamic light scattering (DLS) and electrophoretic mobility, while encapsulation efficiency (EE) and PG content were determined by previously validated ultra-high-performance liquid chromatography (UHPLC) methods.The optimized formulation (NPPG) was further characterized using field-emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), and Fourier-transform infrared spectroscopy (FTIR), in addition to stability studies conducted at different temperatures over a period of 120 days. In vitro drug release was evaluated at pH 4.0 and 7.5 using mathematical modeling to elucidate the release kinetics. Mucoadhesive properties were assessed in vitro by measuring binding efficiency (BE%) and analyzing physicochemical changes upon contact with varying concentrations of mucin.The results demonstrated that nanoparticles were successfully obtained using the proposed methodology. The optimized formulation, containing 25 mg of CS and 10 mg of PG, exhibited spherical morphology, a smooth and regular surface, and nanometric size, consistent with DLS findings, which indicated an average diameter of 256.03 nm, monodispersity (PDI = 0.335), a positive zeta potential of +19.93 mV, high encapsulation efficiency (98.51%), and PG content of 2.11% (equivalent to 20 mg/g). XRD analysis suggested that the encapsulation process resulted in PG amorphization, whereas FTIR analysis confirmed successful drug entrapment within the hybrid nanoparticles.Stability studies identified 4 °C as the most suitable storage condition, effectively preserving the physicochemical properties of NPPG (p > 0.05). In vitro release studies demonstrated a controlled release profile, with 73.94% and 48.56% of PG released at pH 4.0 and 7.4, respectively, after 12 hours. Release kinetics were best described by the Korsmeyer–Peppas model (R² = 0.9961 at pH 4.0; R² = 0.9732 at pH 7.4) and the Weibull model (R² = 0.9849 at pH 4.0; R² = 0.9267 at pH 7.4), indicating Fickian diffusion and parabolic release mechanisms (n < 0.45; b < 1) under both conditions. In vitro mucoadhesion assays confirmed the mucoadhesive potential of NPPG, attributed to the presence of chitosan, as evidenced by an increase in mean particle size and a shift from positive to negative surface charge upon exposure to mucin. The highest binding efficiency (27.97 ± 0.69%) was observed at a mucin concentration of 0.25 mg/mL. Collectively, the findings provide a robust experimental basis supporting the use of hybrid lecithin–chitosan nanoparticles as a viable, attractive, and innovative strategy for vaginal delivery of progesterone.
Keywords: nanotecnologia; mucosa vaginal; mucosa vaginal; nanopartículas híbridas; hormônio esteroide; nanotechnology; vaginal mucosa; factorial design; hybrid nanoparticles; steroid hormone; Farmacêuticas